The distributional impacts of fiscal policy: The case of the Philippines - Hyun H. Son (Asian Development Bank (ADB), 2022)
The distributional impacts of fiscal policies are instrumental in reducing inequality in countries like the Philippines, where inequality has been persistently high. This paper assesses how equitable various taxes and transfers in the Philippines are by deriving the elasticities of Atkinson and Sen's social welfare functions and introducing a welfare reform index. Among various income sources, the paper finds that rentals from properties, dividends from investment, incomes from construction entrepreneurial activities, and remittances from abroad are regressive. In contrast, family sustenance activities, entrepreneurial activities in farming and fishing, and remittances from domestic sources are found to be progressive. The paper also finds that while direct taxes like personal income tax are overall progressive in the Philippines, they only generate little revenues, indicating their limited impact on inequality reduction. Furthermore, this paper shows that the poor bear much of indirect tax burden on individual commodities such as food items largely consumed at home since they spend a greater proportion of their expenditure on such basic commodities relative to their nonpoor counterparts.
Keywords: H23; H24; H31; H53; I38; 330; social welfare function; tax progressivity; redistribution; normative analysis; horizontal inequity; fiscal policy